Analyzing The Impact of Outbound Training to Increase Teamwork Among Students: A Systematic Literature Review - Ramadhani, Azzahra Agustin Sri; Kinasih, Kannindya Sekar; Fauziah, Laili Indah; Tristan, Muhammad; Istiqomah, Mutiara Titian; Muhammad, Naufalsyah Falah; Fanani, Erianto; Aditya, Ronal Surya (Tarqabin Nusantara Group, 2023)
A team can be said to be successful if there are tricks in it to achieve that success. In running a game, a team must be able to achieve success. One trick that can be done to achieve this success is good teamwork and cooperation. In this case, a team, to achieve success, is expected to do something together by helping each other as a team or group. In the research of this article, six literature reviews were used, and keywords for each data were used to search the Google Scholar and ResearchGate bases from 2018 to 2023. A result of this literature review explains how the results of teamwork achieve success. From the topics that have been found, we get topics such as the importance of teamwork to increase self-confidence, courage, creative thinking, team unity, effective communication, responsibility, cooperation and trust between team members. The success of a team is obtained by good and cooperative cooperation so that it will create the ability to train confidence, courage, creative thinking, and team unity.